THE PERCEPTION OF AESTHETIC ASPECTS IN PAEDIATRIC PATIENTS - A SCOPING REVIEW - Laura Zaharia; Alexandru Grațian Grecu; Anca Ștefania Mesaroș; Alexandra Iulia Aghiorghiesei; Raul Sorin Ghiurca; Diana Dudea (Romanian Society of Oral Rehabilitation, 2023)
Aim of the study To review the characteristics of aesthetic perception in pediatric patients regarding different dental medicine fields. Material and methods A literature search on PubMed and ScienceDirect has been performed using the following key terms:"pediatric", "aesthetics", "dental," and "perception". The inclusion criteria were represented by: recent studies between 2015 and 2023, published in the English language, studies regarding pediatric aesthetic aspects, and 6 to 18 years the subjects' age (childhood through adolescence). Studies that did not meet inclusion criteria were excluded from this review. As a result, a number of 51 articles were selected. Results The selected articles (N=51) were grouped into five categories, as follows: the perception of aesthetic aspects regarding dental issues: colour, number, shape, size, and structure in pediatric dentistry (N=17); dentofacial aesthetics (N=7); the impact of dentofacial aesthetics on health-related quality of life in children (N=13); aesthetics of dental prosthetics and restorations in pediatric dentistry (N=5); and aesthetic aspects of orthodontic treatment and malocclusion (N=9). Conclusions Pediatric patients are aware of many aspects of dentofacial aesthetics; behavioral and psychosocial changes were demonstrated among children and adolescents dissatisfied with the shape of the face, the appearance of the smile, facial symmetry, and the aspects of the lips, chin, nose, or cheeks. Further research is still necessary regarding the perception and self-perception of the aesthetic expectations of dental treatments for children of 3-6 years old age group.